Філософія держави: проблеми наукової ідентифікації - Бостан, С.; Bostan, S. (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті проаналізовані наявні в сучасній науці підходи до вивчення проблем, пов'язаних з державою, та обґрунтована необхідність її філософського осмислення в рамках нової наукової дисципліни– філософії держави. Запропоновано визнати за філософією держави статус автономної дисципліни з міждисциплінарним компонентом (філософії і державознавства), предметом якої є пізнання феномену держави на основі гносеологічних, онтологічних та аксіологічних засад. The article analyzes the existing in modern science approaches to the study of the issues related to the state, laying emphasison the necessity of philosophical interpretation of these issues within a new scientific discipline - philosophy of the state. The author suggests to begin with the recognition of the autonomous status of the interdisciplinary subject of philosophy of the state when defining content structure and logic arrangement of its elements. The content of the discipline should be considered on the basis of the triunity of epistemological, ontological and axiological foundations of the state. The article highlights the prospects of institutionalizing the philosophy of the state as an ideological discipline that contributes to the process of fundamentalization of science and higher education in the modern world. The formationof the specific branch of science about state «state studies» has been determined as a promising direction for further research and philosophy of the state would lay philosophical foundation of the new scope of scientific investigation.
Problems of Scientific Identification
Keywords: філософія; філософія держави; наука про державу; наукова ідентифікація; інституціоналізація; державознавство; philosophy; philosophy of the state; science about the state; scientific identification; institutionalization